CANELA: An AI-Driven Edge Camera System for Active Object Tracking in Intelligent Surveillance Systems - Silva, José Manoel; Lima, Leonardo; Loss, Stefano; Batista, Thais; Cavalcante, Everton; Rocha Neto, Aluizio; Araújo, Daniel; Cunha, Eduardo Nogueira; Cacho, Nélio; Lopes, Frederico (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
Intelligent surveillance systems have been increasingly relying on edge-based Artificial Intelligence for real-time object detection and tracking. However, fixed cameras suffer from a limited field of view and degraded image quality at long distances, while resource-constrained edge devices struggle to run complex vision models without incurring high latency and thermal issues. This paper presents CANELA (Camera with Autonomous Navigation and Envisioning Led by AI), a low-cost pan-tilt edge camera system for active object tracking. CANELA combines a custom gimbal, parallel control algorithms, and a Raspberry Pi 5 with a Hailo-8L M.2 Entry-Level accelerator to enable efficient on-device inference and dynamic camera repositioning to keep targets centered. Experimental results in a face-detection pipeline leveraging hardware acceleration demonstrate that CANELA maintains high frame rates while preserving CPU availability by offloading neural network inference to the accelerator. Compared to fixed cameras, it increases the duration of high-quality target capture, improving detection performance and tracking stability.